First stratigraphically complete Coniacian-Santonian boundary record from the Ruvuma Basin (southern Tanzania, East Africa): planktonic foraminiferal, geochemical and paleoceanographic patterns - M.R. PETRIZZO; A. Jiménez Berrocoso; F. Falzoni; B. T. Huber; K. G. MacLeod (2016)
A 101-m-thick stratigraphically complete late Coniacian - early Santonian (89-83 Ma) sedimentary sequence drilled in Tanzania allows examination, for the first time, of the planktonic foraminiferal biostratigraphy, foraminiferal evolution, depositional history and geochemical patterns from the subtropical-tropical Indian Ocean spanning this interval. Planktonic foraminifera at Tanzania Drilling Project (TDP) Site 39 are diverse and the occurrences of Tethyan marker species enable application of the tropical biozonation. The topmost 70.18 m of the section are assigned to the Dicarinella asymetrica Zone, while the underlying sediments belong to the Dicarinella concavata Zone. In addition, TDP 39 is proposed as reference section for the Coniacian/Santonian boundary in the Indian Ocean with the boundary placed at the lowest occurrence of Globotruncana linneiana in agreement with the sequence of events defined at the GSSP stratotype section in Spain. The sedimentary record at TDP 39 was deposited in an outer shelf to upper slope setting dominated by calcareous clayey siltstones and mudstones and, thus, provides a unique opportunity to document the planktonic foraminiferal evolution in a subtropical marginal sea environment. Specifically, the Coniacian-Santonian interval represents a key-period in the evolutionary history of planktonic foraminifera during which deep dwelling taxa underwent a major radiation (originations outnumbered extinctions) that has been related to a series of climatic and oceanographic changes. Combined documentation of lithological and geochemical data from TDP 39 reveal a paleoceanographic history influenced first by a high transfer of continental-derived nutrients to surface waters in the D. concavata Zone that shifts to higher carbonate production and reduced surface water primary productivity in the overlying D. asymetrica Zone. Planktonic foraminiferal assemblage changes mirror the depositional and geochemical trends and indicate a progressive change from a more eutrophic to a more ...